Monitoring trade in plastic waste and scrap - Brown, Andrew (OECD Publishing, 2023)
Global trade in plastic waste and scrap declined further (2017-2021) in 2021 and preliminary data indicates a continuing trend in the first half of 2022 (January to May). The combined trade surplus of OECD Member Countries (i.e., the difference between exports and imports) continued to decrease. Less plastic waste and scrap is being exported by OECD countries to non-OECD countries, however some countries still export substantial volumes to non-OECD countries. Particularly several non-OECD south-east Asian countries remain large export destinations. At the same time, trade between OECD countries has increased. The value and composition of plastic waste and scrap exports in 2021 suggests that more high value and easy to recycle plastic waste was traded. The trade regime remains dynamic with new export destinations emerging, which deserve further monitoring
Keywords: Environment